Hemodynamic effect of Patent Ductus Asteriosus (PDA) - Kori, Mohamad Ikhwan (2015)
Patent ductus arteriosus (PDA) is a condition in which the patent ductus arteriosus remain patent after birth, causing the blood to shunt through the ductus arteriosus. Thus it is very crucial to determine the flow conditions while the shunting process is outgoing. The objective of this research is to identify the abnormality of hemodynamic which includes the flow rate percentage in different PDA morphologies. Three patient-specific PDA morphologies have been identified and modelled using MIMICS and Solidworks. The blood flow inside the PDA morphologies are investigated numerically using ANSYS CFX 14.0. Four criteria have been identified which are the flow characteristic, time-averaged wall shear stress (TAWSS), oscillatory shear index and mass flow rate. Flow recirculation with low velocity and low TAWSS has been identified at the proximal wall of the aortic branches and PDA, and the region of the insertion of PDA at pulmonary artery. High velocity blood flow and high TAWSS mainly focused on the distal wall of the aortic branches and PDA, and the distal of pulmonary artery, after the insertion of PDA to the pulmonary artery. High OSI value is identified at outer wall of the ascending aorta, at the PDA wall and at the pulmonary artery, especially at the region of the insertion of PDA at the artery and the distal of the left pulmonary artery. DS LPA has the highest percentage of wall area covered by OSI larger than 0.2, approximately around 50%. Lastly the PDA morphologies simulated exhibit a left-to-right shunt, which diverts approximately 10% of blood flow from the aorta to the pulmonary artery. The highest shunted blood flow is found in TR LPA morphology.